The Effect Of Planting Distance On The Growth And Yield Of Cabbage (Brassica oleracea L.) In The Lowland's Klamalu Village, Mariat District, Sorong Regency - Akhmad ali; Nurul Fajeriana (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2022)
The decline in production of cabbage in Indonesia is due to the lack of intensive and traditional cultivation of this plant, ie without the use of spacing and frequency that is not appropriate, resulting in a seizure of nutrients from the soil by plants and organ cover of the cabbage plant itself which inhibits the photosynthesis process. So this research was conducted to know the effect of effective spacing that can increase the growth and production of cabbage plants. This study used a single factor randomized block design consisting of 4 levels of treatment, namely 1) Without Planting Distance; 2) Planting distance 35 cm x 35 cm; 3) Distance to plant 45 cm x 45 cm; and 4) Planting distance 55 cm x 55 cm. Each treatment was repeated 3 times to obtain 12 experimental units. The plant spacing factor on cabbage had a significant effect on the observation of plant height, the number of leaves, and leaf length. While the results of observations on the fresh weight of cabbage buds did not have a significant effect on the spacing treatment. The planting distance at 25cm x 55cm gave the best effect on the growth and production of cabbage (Brassica oleraceae L.).